2017
DOI: 10.1177/0735633116686082
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Parents’ Conceptions of Augmented Reality Learning and Approaches to Learning by Augmented Reality With Their Children

Abstract: With the increasing attention to the role of parents in children's learning, what issues parents consider and how they behave when learning with their children when confronted with the emerging augmented reality (AR) technology may be worth exploring. This study was therefore conducted to qualitatively understand parents' conceptions of AR learning and approaches to learning by AR with their children. A total of 90 pairs of parents and children were invited to participate in an AR book reading activity held in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 36 publications
0
15
0
3
Order By: Relevance
“…It was also found that parents who held higher-level conceptions (e.g., learning by AR as increasing the interaction between learners and learning materials) may have used more advanced strategies to learn with their children (e.g., discussing the learning content with their children in order to help their children's reflection on the content learned previously), and vice versa. Interestingly, in that study (Cheng, 2017), for those parents with negative conceptions, they may have thought more critically rather than superficially about the disadvantages of AR learning, and therefore tended to utilize more advanced strategies. To some extent, the findings imply the relationships between individuals' conceptions of learning and the way they learn.…”
Section: Conceptions Of Learning By Armentioning
confidence: 80%
See 2 more Smart Citations
“…It was also found that parents who held higher-level conceptions (e.g., learning by AR as increasing the interaction between learners and learning materials) may have used more advanced strategies to learn with their children (e.g., discussing the learning content with their children in order to help their children's reflection on the content learned previously), and vice versa. Interestingly, in that study (Cheng, 2017), for those parents with negative conceptions, they may have thought more critically rather than superficially about the disadvantages of AR learning, and therefore tended to utilize more advanced strategies. To some extent, the findings imply the relationships between individuals' conceptions of learning and the way they learn.…”
Section: Conceptions Of Learning By Armentioning
confidence: 80%
“…A recent study explored parents' conceptions of AR learning (e.g., Cheng, 2017) and identified eight hierarchical categories of their conceptions. That is, the parents considered learning by AR as (1) increasing presence, (2) drawing attention, (3) fostering motivation, (4) extending content, (5) attaining in-depth understanding, (6) enhancing interaction, (7) obstructing reading, and (8) diminishing imagination.…”
Section: Conceptions Of Learning By Armentioning
confidence: 99%
See 1 more Smart Citation
“…Location-based AR recognises where the user is positioned and provides virtual information which seamlessly blends with the physical environment of the users (e.g., the game Pokemon Go developed by Niantic). Image-based AR utilises graphics identification techniques to identify plain images within the real world and then provides to users synthetic information or other elements intersecting with the plane images [51].…”
Section: Contemporary Multimodal Learning: Augmented Reality and Serimentioning
confidence: 99%
“…Technology integration in education is mandated by programs of study in Canada and in many other places around the world. Advocates of technology integration extol improved student achievement (Butzin, 2001), heightened motivation and engagement (Cheng, 2017;Norris, Sullivan, Poirot, & Solloway, 2003;Passey, Rogers, Machell, McHugh, & Allaway, 2003), and performance in curricular areas such as in Language Arts (e.g., Andresen, 2017;Curcic & Johnstone, 2016;Lopez, 2010;Maher, 2011). Canadian research has also reported similar perceived benefits to students' learning and teachers' instruction (Froese-Germain, Reil, & McGahey, 2013); however, the presence of technology neither ensures it is integrated effectively nor used to promote pedagogically appropriate practices (Bauer & Kenton, 2005;Hooper & Rieber, 1999) and new technologies are often used to replicate traditional delivery methods such as blackboards (Beauchamp, 2004;Serow & Callingham, 2011) or drill-and-practice worksheets (Franklin, 2007).…”
Section: Introductionmentioning
confidence: 99%